Rethinking Law and Justice: The Core Principles of Critical Legal Studies against Legal Formalism - Setyawan, Vincentius; Bariah Safrut (NUSANTARA: Journal Of Law Studies, 2025)
The core idea of Critical Legal Studies is that law is not a neutral and objective system but is influenced by social, political, and economic factors. This perspective challenges the Legal Formalism doctrine, which holds that the law should be applied consistently in accordance with existing rules, without regard to social or political context. This article will explore the key ideas of Critical Legal Studies and its critique of the Legal Formalism school of thought. The article is written based on research using a normative legal research method with a philosophical approach. The research findings highlight that Critical Legal Studies' critique of Legal Formalism begins with the reality that its implementation leads to law enforcement that neglects the values of justice, equality, and equity in everyday life. Critical Legal Studies seeks to establish a legal system that is more just and responsive to the public's need for justice in their daily reality. This study contributes to legal theory by reaffirming that law cannot be separated from its socio-political and economic contexts. Through a normative legal research method with a philosophical approach, this article reconstructs the understanding of justice beyond the rigidity of Legal Formalism. It highlights that the Critical Legal Studies movement provides a transformative framework for developing a more contextual, equitable, and human-centered legal system, offering a significant alternative paradigm within contemporary legal philosophy.